2017
DOI: 10.1007/s00198-017-4026-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two automated assays of BTM (CTX and P1NP) and reference intervals in a Danish population

Abstract: There is significant disagreement between the IDS-iSYS and Roche Cobas assays for both reference markers. Consequently, the reference intervals for an adult, healthy population are different depending on the analysis method used. Therefore, repeated measurements of patient samples used for monitoring of treatment should be done on the same assay. Moreover, assay-specific reference intervals should be used. Harmonization of assays for BTM is highly warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 29 publications
3
31
1
1
Order By: Relevance
“…However, the actual status of bone turnover in OA remains unclear and the few studies on bone turnover markers in OA are conflicting showing either reduced or increased CTX and unchanged PINP . Our data indicated that bone resorption (CTX) was low to low normal (mean: 269 ng/L) compared to the reference interval established by Jorgensen et al, while bone formation (PINP) was within normal range (mean: 42.5 µg/L).…”
Section: Discussioncontrasting
confidence: 46%
“…However, the actual status of bone turnover in OA remains unclear and the few studies on bone turnover markers in OA are conflicting showing either reduced or increased CTX and unchanged PINP . Our data indicated that bone resorption (CTX) was low to low normal (mean: 269 ng/L) compared to the reference interval established by Jorgensen et al, while bone formation (PINP) was within normal range (mean: 42.5 µg/L).…”
Section: Discussioncontrasting
confidence: 46%
“…Thus, the decrease could be an age-related phenomenon, or due to the change of assays. It is worth noting that our follow-up CTX values are at the very low end of the newly suggested normal range for a Danish population (41) .…”
Section: Calcium and Bone Turnover Parametersmentioning
confidence: 53%
“…The present study focused on bone metabolism indicators in patients of different age and gender using HIS data from one hospital, providing mathematical modeling to assist the future study of age and gender in disease research. Although multiple studies have been published that provide a reference for differences in children and adolescents [2][3][4][5][6][7][8], those studies did not provide a precise breakdown of age and gender, namely at what patient age does parameters require precise matching and which age does they not. Researchers believe that age matching should be performed on all subjects in disease control research, but strict age-matching substantially increases the cost and di culty of conducting the study.…”
Section: Discussionmentioning
confidence: 99%